Dampak Media Pembelajaran Video Berbasis STEM terhadap Peningkatan Literasi Sains Tata Surya pada Siswa Slow Learner : The Impact of STEM-Based Video Learning Media on Improving Solar System Science Literacy among Slow Learners - Jayanti Evie Nopitasari; Siti Rohmah Nurhayati (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study aims to determine the impact of using STEM-based video learning media on improving the scientific literacy of slow-learning 7th-grade students at SMPIT Daarussallam regarding the solar system topic. Low scientific literacy among slow learners poses a challenge in science education, particularly with the solar system topic, which involves abstract concepts that are difficult to grasp through conventional teaching methods. Therefore, there is a need for learning media capable of presenting concepts visually, concretely, and contextually, in alignment with the students' learning characteristics. This study employs a quantitative approach using a quasi-experimental method and a One-Group Pretest-Posttest design. The study population consists of all nine slow-learning 7th-grade students at SMPIT Daarussallam during the 2025/2026 academic year; a total sampling technique was used, meaning the entire population served as the research sample. The research instrument was a scientific literacy test on the solar system, administered before (pretest) and after (posttest) the intervention. Data were analysed using descriptive statistics and the Paired Sample t-Test. The results indicate that the average pretest score of 46.33 increased to 86.56 in the posttest. The Paired Sample t-Test results showed a significance value (Sig. 2-tailed) of 0.000 (<0.05), demonstrating a significant improvement in scientific literacy following the implementation of the STEM-based video learning media. Thus, STEM-based video learning media is effective for enhancing the scientific literacy of slow-learning students regarding the solar system by presenting concepts in a manner that is more concrete, engaging, and suited to the students' learning needs.